A119 THE LOCATION-BASED RESECT AND DISCARD STRATEGY FOR DIMINUTIVE COLORECTAL POLYPS: A PROSPECTIVE CLINICAL STUDY. (4th March 2021) - Taghiakbari, M; Pohl, H; Djinbachian, R; Barkun, A N; Marques, P; Bouin, M; Deslandres, E; Panzini, B; Bouchard, S; Weber, A; von Renteln, D
Abstract: Background: Replacing histopathology evaluation of diminutive polyps with optical polyp diagnosis is considered a cost-effective approach. However, the widespread use of optical diagnosis is limited due to concerns about making incorrect optical diagnoses and the requirements of training, credentialing and auditing of performance. Aims: This prospective study aimed to evaluate a simplified resect and discard strategy that is not operator dependent. Methods: The study evaluated a resect and discard strategy that uses anatomical polyp location to classify colon polyps into non-neoplastic or low-risk neoplastic. All rectosigmoid diminutive polyps were considered hyperplastic and all polyps located proximally to the sigmoid colon were considered neoplastic. Surveillance interval assignments based on these a priori assumptions were compared with those based on actual pathology results and optical diagnosis, respectively. The primary outcome was ≥90% agreement with pathology in surveillance interval assignment. Results: Overall, 1117 patients undergoing complete colonoscopy were included and 482 (43.1%) had at least one diminutive polyp. Surveillance interval agreement between the location-based resect and discard strategy and pathological findings using the 2020 US Multi-Society Task Force guideline was 97.0% (95% CI = 0.96 - 0.98), surpassing the ≥90% benchmark. Optical diagnoses using NICE and Sano classifications reached 89.1% and 90.01% agreement, respectively (p <0.0001), and were inferior to the location-based strategy. The location-based resect and discard strategy allowed a 69.7% (95% CI = 0.67 - 0.72) reduction in pathology examinations compared with 55.3% (95% CI = 0.52 - 0.58) (NICE and Sano) and 41.9% (95% CI = 0.39 - 0.45) (WASP) with optical diagnosis. Conclusions: The location-based resect and discard strategy achieved very high surveillance interval agreement with pathology-based surveillance interval assignment, surpassing the ≥90% quality benchmark and outperforming optical diagnosis in surveillance interval agreement and the number of pathology examinations avoided. Funding Agencies: None